L2 Learners’ Preferences and Opinions of Teachers’ Written Corrective Feedback in L2 Writing Multicultural Class - Sabariah Abd Rahim; Anna Lynn Abu Bakar; Wan Hurani Osman (Secholian Publication (Kuala Lumpur, Malaysia), 2023)
Effective writing skills are essential for second language (L2) learners to achieve. To assist these learners, writing teachers provide methods to improve their skills in writing, and one of the methods is written corrective feedback. Despite applying written corrective feedback, L2 learners still face challenges in developing their writing skills, especially the skill to produce linguistically accurate writing. Written corrective feedback is a form of written feedback that is commonly employed pedagogically in writing class. Nevertheless, it is unsure whether or not L2 learners are benefited from this method. Therefore, this study seeks to determine the preferences and opinions of L2 learners regarding their teachers' written corrective feedback. The study adopted a mixed-methods research method, combining a questionnaire and a semi-structured interview. This study involved twenty-one L2 students from various ethnic backgrounds. The findings indicate that these L2 learners of diverse ethnic backgrounds require written corrections to improve their writing correctness. As a result of the teachers' lack of effort in expressing the written corrective comments, the L2 students are unable to comprehend the corrections made. This impacts their writing accuracy. For this reason, they choose face-to-face consultation for the written CF, as it will benefit both their revisions and future writings. This study is relevant because it provides teachers with insights for enhancing the efficiency of written corrective feedback in an L2 writing class.